FACTORS AFFECTING THE RETENTION OF SPECIAL EDUCATION TEACHERS IN THE USA - Shumaieva, Svitlana (Scientific Journal of Polonia University, 2024)
The aim of this paper is to provide the information about the specifics of the special educators’ work in the United States. The conditions for obtaining a certificate that allows a teacher to hold a relevant position were analised. It was described the types of certificates such as the Early Childhood Certificate, which allows teachers to work with students from birth to preschool age, the Certificate for Working with Children with Mild or Moderate Disabilities, which allows teachers to work with students from kindergarten to 22 years of age, the DoHH Certificate, which allows teachers to work with deaf and hard of hearing children, and the Certificate VI for students who are partially or totally blind. It was given a detailed description of a special teacher’s daily duties, were designated the problems that lead to special educators number decreasing and outlined the ways of the problem solving at different levels.